PL03 Socio-Economic Inequalities in Lung Cancer Treatment: A Systematic Review and Meta-Analysis. (17th September 2012) - Forrest, LF; Adams, JM; Wareham, H; Rubin, G; White, M
Abstract : Background: Intervention-generated inequalities in health result from the way that health interventions are organised and delivered. There is some evidence that socio-economic inequalities in care may occur for some common cancers and treatment inequalities may contribute to socio-economic differences in survival. Although the incidence and outcome of lung cancer varies with socio-economic status (SES), it is not known whether socio-economic inequalities in treatment occur. We conducted a systematic review and meta-analysis of existing research on socio-economic inequalities in receipt of treatment for lung cancer. Methods: Systematic methods were used to identify relevant studies, assess study eligibility for inclusion and evaluate study quality. Cohort studies of adults with a primary diagnosis of lung cancer, published in peer-reviewed English language journals up to 2011, were examined. All studies reporting rates of receipt of any treatment for lung cancer according to a measure of SES were included in the review. Studies that reported odds ratios for receipt of treatment, adjusted for at least age and sex, were included in the meta-analysis. Subgroup analyses by healthcare system (universal healthcare system or insurance-based system), histology and stage were conducted. Results: From the initial 1345 studies identified, 46 studies were included in the review and 29 in the meta-analysis. Socio-economic inequalities in receipt of lung cancer treatment were observed. Low SES was associated with a reduced likelihood of receiving any treatment (OR=0.79, CI (0.74 to 0.84) p<0.001), surgery (OR=0.71 (CI 0.65 to 0.77), p<0.001) and chemotherapy (OR=0.81 (CI 0.73 to 0.91), p<0.001), but not radiotherapy (OR=0.95 (CI 0.84 to 1.07), p=0.41), for lung cancer. The association was found in both insurance-based and universal healthcare systems and remained when stage and histology were taken into account for receipt of surgery. Conclusion: This systematic review and meta-analysis found that lung cancer patients living in more socio-economically deprived circumstances were less likely to receive any type of treatment, surgery and chemotherapy. These inequalities cannot be accounted for by socio-economic differences in stage at presentation or by type of healthcare system. Further investigation is required into the patient, clinician and system factors that may contribute to socio-economic inequalities in receipt of lung cancer care and how these inequalities may impact on survival, and also into how to reduce such inequalities.